Coating type preformed brazing filler metal and preparation method and application thereof

By using coated preformed solder in the liquid injection port of the lithium battery cell, combined with high-frequency induction welding and self-crosslinking emulsion, the defects and low yields in the packaging process of the liquid injection port in the prior art are solved, and efficient and environmentally friendly welding effects are achieved.

CN119635074AActive Publication Date: 2025-03-18SOLDERWELL MICROELECTRONIC PACKAGING MATERIALS CO LTD

Patent Information

Application Number
CN202411992694.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The prior art has defects such as splash, pores, and cracks in the packaging process of lithium battery cell injection ports, resulting in low yields and unsatisfactory in the efficiency and yield of existing induction welding technologies.

Method used

A coated preformed solder is provided, including an aluminum-silicon alloy and a fluoroaluminate flux wrapped around the periphery of the solder, which fills the weld by melting and flow during high-frequency induction welding, combined with a self-crosslinking emulsion to replace the adhesive in the flux, reducing organic decomposition and splashing.

Benefits of technology

It improves welding yield and welding speed, reduces organic matter decomposition and smoke during welding, reduces production costs, and improves safety and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119635074A_ABST
    Figure CN119635074A_ABST
Patent Text Reader

Abstract

The invention discloses coating type preformed brazing filler metal and a preparation method and application thereof, and belongs to the technical field of brazing, the coating type preformed brazing filler metal comprises brazing filler metal and brazing flux wrapping the periphery of the brazing filler metal, the brazing filler metal comprises aluminum-silicon alloy, and the brazing flux comprises fluoroaluminate; the mass ratio of the aluminum-silicon alloy to the fluoroaluminate is (75-96): (4-25). According to the method, the outer surface of the aluminum-silicon alloy is coated with the fluoroaluminate, the brazing flux can effectively remove an oxidation film on the surface of brazing filler metal and an oxidation film on a welding interface, the welding quality is improved, and then the product yield is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brazing, and in particular to a coated preformed brazing filler metal and a preparation method and application thereof. Background Art

[0002] With the vigorous development of the new energy vehicle industry, the lithium battery market has also been growing year by year. Among them, the battery cell is the core component of the lithium battery, and its production capacity and yield rate are also of great concern, which is ultimately related to the price trend of new energy vehicles.

[0003] The production cost of battery cell has been reduced to a certain extent through continuous process improvement. However, the packaging of the liquid injection port has always been a pain point, and the defective rate remains high. The yield of some models of products does not even reach 70%. This is because the existing packaging technology uses laser welding technology, which may produce defects such as spatter, pores, and cracks. Although these defects can be repaired through rework, the production cost is increased. In this regard, some people have begun to consider using induction welding technology to replace laser welding. However, the efficiency and yield of the existing induction welding technology are not satisfactory. Therefore, there is an urgent need for a coated preformed solder suitable for sealing the liquid injection port of the battery cell to solve the problem of low one-time sealing yield of the liquid injection port of the new energy battery cell.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a coated preformed solder and a preparation method and application thereof, which can effectively improve the welding yield and welding speed.

[0006] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a coated preformed solder, comprising a solder and a flux wrapped around the outer periphery of the solder, wherein the solder comprises an aluminum-silicon alloy, and the flux comprises a fluoroaluminate;

[0007] The mass ratio of the aluminum silicon alloy to the fluoroaluminate is (75-96):(4-25).

[0008] As an implementation scheme of the present application, the mass percentage of silicon in the aluminum-silicon alloy is 11-13%.

[0009] As an embodiment of the present application, the mass ratio of the self-crosslinking emulsion to the fluoroaluminate is (0.3-2):100.

[0010] As an embodiment of the present application, the self-crosslinking emulsion includes a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion; the mass ratio of the self-crosslinking acrylic emulsion to the self-crosslinking polyurethane emulsion is (1.5-9):1.

[0011] As an embodiment of the present application, the glass transition temperature of the cross-linked acrylic emulsion is ≤30°C.

[0012] As an embodiment of the present application, the minimum film-forming temperature of the self-crosslinking polyurethane emulsion is ≤0°C.

[0013] In a second aspect of the present application, the present application provides a method for preparing a coated preformed solder, comprising the following steps:

[0014] The flux, the self-crosslinking emulsion and the solvent are uniformly mixed to obtain a mixed solution;

[0015] The mixed liquid is evenly coated on the surface of the solder, and the solvent is removed by drying to obtain a coated preformed solder.

[0016] As an embodiment of the present application, the solvent includes at least one of water, ethanol, n-propanol, propylene glycol, propylene glycol butyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, and dipropylene glycol dimethyl ether.

[0017] As an implementation scheme of the present application, the mass ratio of the solvent to the flux is (0.8-2):1.

[0018] In a third aspect of the present application, the present application provides an application of a coated preformed solder in sealing a liquid injection port of a battery cell.

[0019] As an implementation scheme of the present application, the coated preformed solder is placed above the weld formed by the sealing pin and the battery cell top cover. During the high-frequency induction welding process, after the solder melts, the molten liquid flows downward to fill the weld.

[0020] As an implementation scheme of the present application, at least one of the following (1) to (3) is satisfied:

[0021] (1) The volume of the weld is a1, the volume of the coated preformed solder is a2, and the following conditions are satisfied: 2.17≤a2 / a1≤10;

[0022] (2) The cross-sectional area of ​​the weld is b1, and the cross-sectional area of ​​the coated preformed solder is b2, satisfying: 2≤b2 / b1≤5;

[0023] (3) The height of the coated preformed solder is ≤5 mm.

[0024] In a fourth aspect of the present application, the present application provides a battery cell liquid injection port, comprising the coated preformed solder described above.

[0025] The beneficial effects of the present invention are as follows: (1) the present invention coats the outer surface of the aluminum silicon alloy with fluoroaluminate, and the brazing agent can effectively remove the oxide film on the surface of the brazing material and the oxide film on the welding interface, thereby improving the welding quality and further improving the product yield;

[0026] (2) The present application adds a self-crosslinking emulsion comprising a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion. The self-crosslinking emulsion replaces the adhesive in the flux, thereby reducing the decomposition and splashing of organic matter during the welding process. Therefore, after welding, there is no need to clean the weldment, welding equipment and fixtures, etc., and at the same time, it can reduce the decomposition of organic matter and the amount of smoke during the welding process, thereby improving safety and environmental protection. The self-crosslinking acrylic acid is easily connected with the hydroxyl group in the flux during the film-forming process to form a coating on the metal surface. The self-crosslinking polyurethane emulsion and the self-crosslinking acrylic emulsion work together to improve the adhesion and welding performance of the flux to the metal, effectively avoid the decline in coating firmness and welding performance, and effectively improve the product yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The schematic diagram is a diagram of welding the weld of the liquid injection port of a battery cell using the coated preformed solder of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0029] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0030] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0031] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0032] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.

[0033] The inventors of the present invention have found that the purpose of prefabricating the solder into a specific shape is to better fill the weld and improve the production yield, while the flux pre-wrapped on the outer surface is to improve production efficiency and yield. The existing induction welding technology generally uses a mixture of flux and solvent to apply before induction welding, and welding is performed in a wet state. The volatilization of the solvent and the instability of the application amount will both result in a reduction in production yield.

[0034] Therefore, in order to solve the above technical problems, the embodiment of the present application provides a coated preformed solder, comprising a solder and a flux wrapped around the outer periphery of the solder, wherein the solder comprises an aluminum-silicon alloy, and the flux comprises a fluoroaluminate;

[0035] The mass ratio of the aluminum silicon alloy and the fluoroaluminate is (75-96):(4-25), for example, it can be 75:25, 76:24, 78:22, 80:20, 82:18, 85:15, 88:12, 90:10, 92:8, 95:5, 96:4 or a range consisting of any two of the values.

[0036] In this application, fluoroaluminate is coated on the outer surface of the aluminum-silicon alloy. The flux can effectively remove the oxide film on the surface of the solder and the oxide film on the welding interface, improve the welding quality, and thus improve the product yield. However, too high a flux will not improve the welding quality, but will lead to an increase in cost. The current cost price of cesium fluoroaluminate flux is about 1 yuan / g, which is not allowed in the cost-sensitive new energy vehicle industry chain.

[0037] In one embodiment, the mass percentage of silicon in the aluminum-silicon alloy is 11-13%, for example, it can be 11%, 11.2%, 11.5%, 11.8%, 12%, 12.2%, 12.5%, 13% or a range consisting of any two of these values.

[0038] In one embodiment, the mass ratio of the self-crosslinking emulsion to the fluoroaluminate is (0.3-2):100, for example, it can be 0.3:100, 0.5:100, 0.6:100, 0.8:100, 1:100, 1.2:100, 1.5:100, 1.8:100, 2:100 or a range consisting of any two of these values. By controlling the mass ratio of the self-crosslinking emulsion to the fluoroaluminate within this range, the coating firmness and welding performance can be improved, powder loss during the coating process can be avoided, and the amount of welding smoke can be effectively reduced.

[0039] In one embodiment, the self-crosslinking emulsion includes a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion; the mass ratio of the self-crosslinking acrylic emulsion and the self-crosslinking polyurethane emulsion is (1.5-9):1, for example, it can be 1.5:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or a range consisting of any two of the values.

[0040] The present application creatively adds a self-crosslinking emulsion comprising a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion. The self-crosslinking emulsion replaces the adhesive in the flux, thereby reducing the decomposition and splashing of organic matter during the welding process. Therefore, after welding, there is no need to clean the weldment, welding equipment, and fixtures, etc., and at the same time, it can reduce the decomposition of organic matter and the amount of smoke during the welding process, thereby improving safety and environmental protection. The self-crosslinking acrylic acid is easily connected with the hydroxyl group in the flux during the film-forming process to form a coating on the metal surface. The self-crosslinking polyurethane emulsion and the self-crosslinking acrylic emulsion work together to improve the adhesion and welding performance of the flux to the metal, effectively avoid the decline in coating firmness and welding performance, and effectively improve the product yield.

[0041] The inventors of the present application have found that when a common solvent such as ethanol is used for pre-coating, the flux pre-coated on the surface is easy to fall off after drying, which will reduce the product yield, so the self-crosslinking emulsion needs to be fixed. Too high a proportion of the self-crosslinking emulsion will also lead to a decrease in product yield, and the proportion of the solvent has no obvious effect within a certain range.

[0042] In one embodiment, the glass transition temperature of the cross-linked acrylic emulsion is ≤30°C.

[0043] In one embodiment, the glass transition temperature of the cross-linked acrylic emulsion is -40 to 30°C, for example, it can be -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C or a range consisting of any two of the values.

[0044] Wherein, the glass transition temperature of the self-crosslinking acrylic emulsion is measured with reference to GB / T 27816 standard.

[0045] In one embodiment, the minimum film-forming temperature of the self-crosslinking polyurethane emulsion is ≤ 0°C.

[0046] In one embodiment, the minimum film-forming temperature of the self-crosslinking polyurethane emulsion is -45°C to 0°C, for example, it can be -45°C, -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 0°C or a range consisting of any two of these values.

[0047] In one embodiment, the minimum film-forming temperature of the self-crosslinking polyurethane emulsion is tested with reference to GB / T9267-2008 standard.

[0048] In one embodiment, the fluoroaluminate comprises CsAlF4, Cs2AlF5, Cs3AlF6, KAlF4, K2AlF5, K3AlF6, K2AlF5·H2O, KCs2Al3F 12 , at least one of CsK2AlF6, KZnAlF6, K2ZnAlF7, KZn2AlF8, KZnAl2F9, CsZnAlF6, Cs2ZnAlF7, CsZn2AlF8, and CsZnAl2F9.

[0049] An embodiment of the present application provides a method for preparing a coated preformed solder, comprising the following steps:

[0050] The flux, the self-crosslinking emulsion and the solvent are uniformly mixed to obtain a mixed solution;

[0051] The mixed liquid is evenly coated on the surface of the solder, and the solvent is removed by drying to obtain a coated preformed solder.

[0052] In one embodiment, the solvent includes at least one of water, ethanol, n-propanol, propylene glycol, propylene glycol butyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, and dipropylene glycol dimethyl ether.

[0053] In one embodiment, the mass ratio of the solvent to the flux is (0.8-2):1, for example, it can be 0.8:1, 1:1, 1.2:1, 1.5:1, 1.6:1, 1.8:1, 2:1 or a range consisting of any two values ​​therein.

[0054] like Figure 1 As shown, one embodiment of the present application provides an application of a coated preformed solder in sealing a liquid injection port of a battery cell.

[0055] In one embodiment, the coated preformed solder is placed above the weld formed by the sealing pin and the battery cell top cover. During the high-frequency induction welding process, after the solder is melted, the molten liquid flows downward to fill the weld.

[0056] In conventional induction welding, the solder is placed at the position of the weld. In the sealing of the sealing pin of the battery cell filling port, the sealing weld area is between the sealing pin and the outside of the filling port. However, this will reduce the welding efficiency due to the induced magnetic field distance. If the induction power is increased, and because the melting points of the sealing pin and the solder are close, the sealing pin above the solder will cause the temperature to rise rapidly under the high-frequency induction power, resulting in burning. Therefore, the solder of the present invention is placed above the sealing pin and is preferentially subjected to induction heating, thereby improving production efficiency and yield.

[0057] The coated preformed solder needs to match the shape of the weld, for example, it can be in the shape of a ring, a square, etc.

[0058] In one embodiment, the volume of the weld is a1, and the volume of the coated preformed solder is a2, which satisfies: 2.17≤a2 / a1≤10, for example, it can be 2.17, 3, 4, 5, 6, 7, 8, 9, 10 or a range consisting of any two values ​​therein. The inventor of the present application has found that the volume of the weld and the coated preformed solder is directly correlated with welding. By controlling 2.17≤a2 / a1≤10, the welding quality and welding yield can be effectively improved. Too low solder volume cannot fill the weld well. After melting, the solder will wet several interface materials at the weld and form a certain wetting angle, which cannot just fill the entire weld. Therefore, it is completely unreasonable to set the preformed solder shape to the pre-filled weld volume, which will cause sealing failure due to the lack of solder flow at some positions, and too high solder volume will cause solder overflow, and also increase the cost of solder and flux. In addition, the solder height exceeds 5mm. , it will cause the solder to not fall vertically into the filling weld during the melting process, resulting in the solder failing to perform a sealing function and reducing the product yield.

[0059] In one embodiment, the cross-sectional area of ​​the weld is b1, and the cross-sectional area (i.e., surface area) of the coated preformed solder is b2, satisfying: 2≤b2 / b1≤5, for example, it can be 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of these values. When the volume of the solder is fixed, if the surface area of ​​the solder changes, it will affect the height of the solder. Too large a surface area will prevent the solder from gathering and flowing into the weld, resulting in part of the solder remaining on the outside of the weld, which will fail to seal and increase the product defect rate. Too small a surface area will cause the solder to be too thick, and the solder may fall outside the injection port during melting, which will also affect the accuracy of assembly and thus affect the product yield.

[0060] In one embodiment, the height of the coated solder preform is ≤5 mm.

[0061] Among them, the parameters of high-frequency induction welding are automatically controlled gradient induction current heating, the first gradient is 100-110A, lasting 4-10s, and the second gradient is 85-95A, lasting 1-2s.

[0062] One embodiment of the present application provides a battery cell liquid injection port, comprising the coated preformed solder described above.

[0063] The sources of raw materials in the embodiments and comparative examples are shown in Table 1.

[0064] Table 1

[0065]

[0066] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.

[0067] Example 1

[0068] A method for sealing a battery core liquid injection port with a coated preformed solder comprises the following steps:

[0069] (1) preparing a coated preformed solder: uniformly mixing cesium fluoroaluminate (CsAlF4), a self-crosslinking emulsion and a solvent to obtain a mixed solution;

[0070] The mass ratio of the self-crosslinking emulsion to cesium fluoroaluminate is 0.3:100; the self-crosslinking emulsion includes a self-crosslinking acrylic emulsion 1 and a self-crosslinking polyurethane emulsion 1 in a mass ratio of 3:1;

[0071] The solvent is n-propanol, and the mass ratio of n-propanol to cesium fluoroaluminate is 1.2:1;

[0072] The mass ratio of cesium fluoroaluminate to AlSi12 is 4:96.

[0073] The mixed liquid is evenly coated on the surface of the solder (AlSi12), and the solvent is removed by drying to obtain a coated preformed solder.

[0074] (2) The coated preformed solder (height of 4 mm) is placed above the weld formed by the sealing pin and the top cover of the battery cell. During the high-frequency induction welding process, gradient induction current heating is used, where the first gradient is 105A for 6 seconds and the second gradient is 90A for 1.5 seconds. After the solder melts, the molten liquid flows downward to fill the weld.

[0075] The volume of the weld is a1, the volume of the coated preformed solder is a2, and a2 / a1=3;

[0076] The cross-sectional area of ​​the weld is b1, the cross-sectional area of ​​the coated preformed solder is b2, and b2 / b1=3.

[0077] The welding parameters are shown in Table 1.

[0078] Examples 2 to 4, Comparative Examples 1 to 2

[0079] The difference between Examples 2 to 4 and Comparative Examples 1 to 2 and Example 1 is that the mass ratio of CsAlF4 and AlSi12 is changed.

[0080] Embodiments 5 to 8

[0081] The difference between Examples 5 to 8 and Example 1 is that the mass ratio of the self-crosslinking emulsion to CsAlF4 is changed.

[0082] Embodiments 9 to 14

[0083] The difference between Examples 9 to 14 and Example 1 is that the mass ratio or type of the self-crosslinking emulsion is changed.

[0084] Embodiments 15-16

[0085] The difference between Examples 15 and 16 and Example 1 is that the mass ratio of the solvent to CsAlF4 is changed.

[0086] Embodiment 17

[0087] The difference between Example 17 and Example 1 is that the type of solvent is changed.

[0088] Examples 18 to 21

[0089] The difference between Examples 18 to 21 and Example 1 is that b2 / b1 is changed.

[0090] Embodiments 22 to 25

[0091] The difference between Examples 22 to 25 and Example 1 is that a2 / a1 is changed.

[0092] Comparative Example 3

[0093] The difference between Comparative Example 3 and Example 1 is that an equal amount of polyacrylic acid is used to replace the self-crosslinking emulsion.

[0094] Comparative Example 4

[0095] The difference between Comparative Example 4 and Example 1 is that no self-crosslinking emulsion is added in Comparative Example 4.

[0096] Comparative Example 5

[0097] A method for sealing a battery core liquid injection port with a coated preformed solder comprises the following steps:

[0098] (1) A coated preformed solder is prepared by manual coating, wherein the coated preformed solder is AlSi12.

[0099] (2) The coated preformed solder (height of 4 mm) is placed above the weld formed by the sealing pin and the top cover of the battery cell. During the high-frequency induction welding process, gradient induction current heating is used, where the first gradient is 105A for 6 seconds and the second gradient is 90A for 1.5 seconds. After the solder melts, the molten liquid flows downward to fill the weld.

[0100] The volume of the weld is a1, the volume of the coated preformed solder is a2, and a2 / a1=3;

[0101] The cross-sectional area of ​​the weld is b1, the cross-sectional area of ​​the coated preformed solder is b2, and b2 / b1=3.

[0102] Table 2

[0103]

[0104]

[0105] Performance Testing

[0106] Production efficiency: the number of devices produced per minute (PPM).

[0107] Yield: The soldered device has no obvious burn damage on the surface, the solder is completely wetted, and when the device is passed through a gas with a pressure of 3kPa and no obvious bubbles are generated in the water, it is considered a good product. 100 devices are tested to determine the yield.

[0108] Coating firmness: The flux obtained in the embodiment and the comparative example are respectively coated on the AlSi12 preformed welding sheet in the same manner to obtain a coated sheet; 50g±0.2g of the coated sheet is taken and placed in the same position in the vibration plate; the material is fed 12 times under the same parameters, the mass of the coated sheet after feeding 12 times is weighed, and the powder loss rate of the coated sheet is calculated. The calculation formula of the powder loss rate of the coated sheet is: Powder loss rate of coated sheet = (coating amount of flux before feeding - coating amount of flux after feeding) ÷ coating amount of flux before feeding; The smaller the powder loss rate of the coated sheet, the better the scratch resistance and adhesion performance of the coated sheet.

[0109] Welding smoke quantity and black residue: The flux obtained in the embodiment and comparative example is coated on the AlSi12 preformed welding sheet to obtain a coated sheet; the coated sheet is heated at a temperature 40°C higher than the melting point of the activator for 5s, and the aluminum parts are welded. During the welding process, the smoke size is measured at 10cm above the welding sheet using an explosion-proof dust meter. Each flux is measured five times and the average value is taken; the average smoke concentration generated when there is only an activator is taken as the reference value, and the average smoke concentration / reference value of each flux is taken as the welding smoke quantity, that is, the relative size of the smoke. Five coated sheets are placed on a pure aluminum plate without other items on it, and heated at 40°C higher than the melting point of the activator for 5s to observe whether there is black residue.

[0110] Table 3

[0111]

[0112]

[0113] It can be seen from Table 3 that the coated preformed solder of the present invention can effectively improve the welding yield and welding speed, reduce the powder loss rate of the coating sheet, and reduce the amount of welding smoke. It can be well applied to the weld welding and sealing of the battery cell injection port, and has broad application prospects.

[0114] By comparing Example 1 with Comparative Examples 1 to 2, it can be seen that the present invention effectively improves the welding yield, reduces the powder loss rate of the coating sheet, and reduces the amount of welding smoke by controlling the mass ratio of aluminum silicon alloy and fluoroaluminate to (75-96): (4-25).

[0115] By comparing Example 1 with Comparative Examples 3 to 4, it can be seen that the present invention effectively improves the welding yield, reduces the powder loss rate of the coating sheet, and significantly reduces the amount of welding smoke by adopting the self-crosslinking acrylic emulsion and the self-crosslinking polyurethane emulsion in a ratio of (1.5 to 9):1.

[0116] It can be seen from the comparison of Examples 1 to 4 that by controlling the mass ratio of aluminum silicon alloy to fluoroaluminate to (8 to 20): (80 to 92), the welding yield is further improved, the powder loss rate of the coating sheet is reduced, and the amount of welding smoke is reduced.

[0117] By comparing Example 1 with Examples 5 to 8, it can be seen that by controlling the mass ratio of the self-crosslinking emulsion to the fluoroaluminate to (0.3 to 2):100, the welding yield is further improved, the powder loss rate of the coating sheet is reduced, and the amount of welding smoke is reduced.

[0118] By comparing Example 1 with Examples 9 to 11, it can be seen that by controlling the mass ratio of the self-crosslinking acrylic emulsion to the self-crosslinking polyurethane emulsion to (3 to 6): 1, the welding yield is further improved, the powder loss rate of the coating sheet is reduced, and the amount of welding smoke is reduced.

[0119] By comparing Example 1 with Examples 12 and 13, it can be seen that by controlling the glass transition temperature of the cross-linked acrylic emulsion to ≤30°C and the minimum film-forming temperature of the self-cross-linked polyurethane emulsion to ≤0°C, the welding yield is further improved, the powder loss rate of the coated sheet is reduced, and the amount of welding smoke is reduced.

[0120] By comparing Example 1 and Examples 18 to 21, it can be seen that by controlling b2 / b1=2 to 5, the welding yield is further improved, the powder loss rate of the coating sheet is reduced, and the amount of welding smoke is reduced.

[0121] By comparing Example 1 and Examples 22 to 25, it can be seen that by controlling a2 / a1=2.17 to 10, the welding yield is further improved, the powder loss rate of the coating sheet is reduced, and the amount of welding smoke is reduced.

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A coated preform solder, characterized in that: The method comprises a brazing material and a brazing flux wrapped around the outer periphery of the brazing material, wherein the brazing material comprises an aluminum-silicon alloy, and the brazing flux comprises a fluoroaluminate; The mass ratio of the aluminum silicon alloy to the fluoroaluminate is (75-96):(4-25).

2. The coated preform solder according to claim 1, characterized in that: The mass percentage of silicon in the aluminum-silicon alloy is 11-13%.

3. The coated preform solder according to claim 1, characterized in that: It also includes a self-crosslinking emulsion, wherein the mass ratio of the self-crosslinking emulsion to the fluoroaluminate is (0.3-2):

100.

4. The coated preform solder according to claim 1, characterized in that: The self-crosslinking emulsion includes a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion; the mass ratio of the self-crosslinking acrylic emulsion to the self-crosslinking polyurethane emulsion is (1.5-9):

1.

5. The coated preform solder according to claim 1, characterized in that: The glass transition temperature of the cross-linked acrylic emulsion is ≤30°C; and / or The minimum film-forming temperature of the self-crosslinking polyurethane emulsion is ≤0°C.

6. The method for preparing a coated preform solder according to any one of claims 1 to 5, characterized in that: The following steps are involved: The flux, the self-crosslinking emulsion and the solvent are uniformly mixed to obtain a mixed solution; The mixed liquid is evenly coated on the surface of the solder, and the solvent is removed by drying to obtain a coated preformed solder.

7. The method for preparing a coated preform solder according to claim 6, characterized in that: The solvent includes at least one of water, ethanol, n-propanol, propylene glycol, propylene glycol butyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, and dipropylene glycol dimethyl ether.

8. The method for preparing a coated preform solder according to claim 6, characterized in that: The mass ratio of the solvent to the flux is (0.8-2):

1.

9. Use of the coated preformed solder according to any one of claims 1 to 5 in sealing the liquid injection port of a battery cell.

10. The use according to claim 9, characterized in that: The coated preformed solder is placed above the weld formed by the sealing pin and the battery cell top cover. During the high-frequency induction welding process, after the solder is melted, the molten liquid flows downward to fill the weld.

11. The use according to claim 10, characterized in that: Satisfy at least one of the following (1) to (3): (1) The volume of the weld is a1, the volume of the coated preformed solder is a2, and the following conditions are satisfied: 2.17≤a2 / a1≤10; (2) The cross-sectional area of ​​the weld is b1, and the cross-sectional area of ​​the coated preformed solder is b2, satisfying: 2≤b2 / b1≤5; (3) The height of the coated preformed solder is ≤5 mm.

12. A battery cell liquid injection port, characterized in that: The invention comprises the coated preformed solder according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Low-melting-point composite self-fluxing aluminum brazing filler metal and preparation method thereof

    CN103769760A

  • Soldering flux which generates few concaves after welding and is used for pre-formed soldering lug

    CN105921911A

  • Environment-friendly corrosion-free self-brazing ring for aluminum alloy brazing and preparation method thereof

    CN107030412A

  • Low-temperature self-brazing flux aluminum-silicon welding ring

    CN107322179A

  • Brazing ring and brazing system

    CN107617829A

Cited By

  • Low-residue soldering flux and preparation method and application thereof

    CN121696597A

  • Low-residue flux and preparation method and application thereof

    CN121696597B

  • Low-residue flux, and preparation method therefor and use thereof

    WO2026060979A1